2022
DOI: 10.3389/fmolb.2022.953048
|View full text |Cite
|
Sign up to set email alerts
|

Using CRISPR/Cas9 genome editing in human iPSCs for deciphering the pathogenicity of a novel CCM1 transcription start site deletion

Abstract: Cerebral cavernous malformations are clusters of aberrant vessels that can lead to severe neurological complications. Pathogenic loss-of-function variants in the CCM1, CCM2, or CCM3 gene are associated with the autosomal dominant form of the disease. While interpretation of variants in protein-coding regions of the genes is relatively straightforward, functional analyses are often required to evaluate the impact of non-coding variants. Because of multiple alternatively spliced transcripts and different transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…We have recently established a novel CCM1 knockout iPSC model and demonstrated that CCM1 −/− iPSCs can be differentiated into ECs which show the upregulation of KLF2 and KLF4 as well as downregulation of THBS1 [ 20 ]. These gene expression differences are well-characterized consequences of CCM1 inactivation in ECs [ 9 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have recently established a novel CCM1 knockout iPSC model and demonstrated that CCM1 −/− iPSCs can be differentiated into ECs which show the upregulation of KLF2 and KLF4 as well as downregulation of THBS1 [ 20 ]. These gene expression differences are well-characterized consequences of CCM1 inactivation in ECs [ 9 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The CCM1 +/+ and CCM1 −/− iPSC lines used in this study were derived from the parental AICS-0023 iPSC line (Allen Cell Collection, Coriell Institute, Camden, NJ, USA) before [ 20 ]. IPSCs were maintained in Essential 8 Flex medium (Thermo Fisher Scientific, Waltham, MA, USA) at 37 °C and 5% CO 2 on plates coated with growth factor reduced Matrigel (Corning, New York, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, they can hardly identify the precise breakpoints of CNVs, pathogenic variants in non-coding regions, and complex structural variants (SVs), e.g., inversions or interchromosomal insertions. This is particularly relevant since all these types of genetic variation have been described for CCM patients in the recent literature [ 6 , 7 , 8 , 9 ]. In the context of analyses for CNVs segregating within CCM families, cost-effectiveness is also an issue.…”
Section: Introductionmentioning
confidence: 99%